Wave transmission analysis of marine structures: Evaluating the accuracy of theoretical models for determining the transmission coefficient - Lundström, Jonathan (My University, 2021)
Analyzing the performance of floating breakwaters is no easy task and there are many different theoretical models, developed to do this. The different theoretical models vary in complexity and are derived for different types of breakwaters. To find the best suiting theoretical model, measurements of the incoming and transmitted wave climate are conducted. In total, 11 different theoretical models and one software, Ansys AQWA, are compared with the measured data. To compare the result from the theoretical models and software with the measured data, the measured data is filtered and averaged over time. The results show that two of the theoretical models correlate well with measured data. The wave measurement data also shows that the breakwater performance is dependent on the incoming wave climate and that the incoming wave climate is dependent on the wind climate. In the study, an IMU sensor is used to measure the movement of the breakwater. By comparing the IMU data with the wave data it is seen that the movement of the breakwater depends on the incoming wave climate. More measurements are needed to evaluate if the movement of the breakwater affects the transmission performance of the breakwater.
Keywords: Wave transmission; Marine structures; Breakwater performance; Transmission models; Transmission coefficient; Wave climate